Reforma do Estado no Brasil (1985-1998): processo decisório em contexto de múltiplos veto players - Maria Jacqueline Nogueira Lima (2007)
The main objective of this paper is to discuss the decision-making process of administrative reform and pension reform during the Fernando Henrique Cardoso in the period 1995-1998, recovering to both our historical roots of state reforms undertaken throughout the twentieth century, with special emphasis on administrative reform as a way to better locate the object and its structural conditions throughout the period, as well as your driving now in democratic contexts, sometimes in authoritarian contexts. In this paper I defend the hypothesis that, despite the Central Executive agenda could have decisive role on the agenda occupying the national political scene, and even the general direction of any changes, the veto players that arise during the analysis process constitutional change, and that are grouped mainly in the legislative branch, have a material impact on the results of decision-making. In view of this we can infer the existence of such veto players is a condition for democratic debate to establish and produce consensual changes in public policies.